2015
DOI: 10.1590/s0102-053620150000400010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e avaliação de progênies autofecundadas de pimenta biquinho salmão

Abstract: Characterization and evaluation of salmon-colored biquinhotype pepper progeniesCapsicum chinense peppers are mostly native to Brazil and the biquinho (beaked)-type C. chinense pepper, aromatic and nonpungent, has been increasing in importance in the Brazilian fresh and pickled pepper market. Despite the increasing demand, a few cultivars are available to growers and breeding programs are required in order to offer interesting cultivars to producers and consumers. This paper reports breeding efforts made on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
1
11
0
3
Order By: Relevance
“…In the present study the production of both cultivars BRS Moema and Airetama biquinho in the E1 season were high (612.81 and 1047.69 g respectively). Heinrich et al (2015) reported highest production averages of 1680 to 1730 g per plant in a cycle for cultivars of orange-colored biquinho pepper. In a study by Empresa Brasileira de Pesquisa Agropecuária -EMBRAPA (2012), cultivars with a red color, such as BRS Moema, with a population of 10,000 plants, can produce 20 t ha -1 , totaling 500 g plant -1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study the production of both cultivars BRS Moema and Airetama biquinho in the E1 season were high (612.81 and 1047.69 g respectively). Heinrich et al (2015) reported highest production averages of 1680 to 1730 g per plant in a cycle for cultivars of orange-colored biquinho pepper. In a study by Empresa Brasileira de Pesquisa Agropecuária -EMBRAPA (2012), cultivars with a red color, such as BRS Moema, with a population of 10,000 plants, can produce 20 t ha -1 , totaling 500 g plant -1 .…”
Section: Discussionmentioning
confidence: 99%
“…is a species that has small round fruits forming a beak. The fruits have low pungency and are characterized as sweet fruits that can be consumed in natura or processed (HEINRICH et al, 2015). Departamento de Fitotecnia, Universidade Federal de Santa Maria (UFSM), 97105-900, Santa Maria, RS, Brasil.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit tip length ( Figure 4D) showed significance only for the absence of mineral fertilization, with a quadratic trend and an ideal dose equivalent to 87 m³ ha -1 of cassava wastewater, with an estimated length of 8.4 mm. A study conducted by Heinrich et al (2015) recorded a variation of 1.5-6.3 mm in the fruit tip length in self-fertilized salmon-colored C. chinense.…”
Section: Svmentioning
confidence: 99%
“…The biquinho pepper is one of the most used varieties by small producers seeking high productivity, acceptance by the consumer market and good financial return, being attractive mainly for its mild taste and absence of pungency (Alves et al 2016;Heinrich et al 2015). According to the above, this work aimed to evaluate the soil chemical parameters and the microbiological quality of the biquinho pepper fruits irrigated with treated wastewater and different irrigation depths.…”
Section: Introductionmentioning
confidence: 99%